Total serum IgE levels as predictor of the acquisition of tolerance in children with food allergy: Findings from a pilot study - Dodi, Giulia; Di Filippo, Paola; Di Pillo, Sabrina; Chiarelli, Francesco; Attanasi, Marina (Frontiers in Pediatrics, 2022)
The gold standard to diagnose food allergy (FA) is a double-blind, placebo-controlled food challenge (OFC), even if it shows potential risk of severe allergic reactions for the patient and is time-consuming. Therefore, easier, and less invasive methods are needed to diagnose FA and predict the tolerance, changing the clinical practice. The main aim of this study was to assess whether the total IgE values at the diagnosis of FA were associated with the duration of the tolerance acquisition and thusof the food elimination diet. We retrospectively analyzed the medical records of 40 patients allergic to milk or egg who performed an OFC for the reintroduction of the causal food at the Pediatric Allergy and Respiratory Unit of the University of Chieti from January 2018 to December 2020. We found a positive association of total serum IgE with the elimination diet duration (β = 0.152; CI 95% 0.04-0.27) after adjusting for age, sex, and type of allergy (milk or egg). We also showed a significant correlation (r = 0.41 and p-value = 0.007) between the total IgE values and the duration of the elimination diet. and a significant correlation between the casein specific IgE values at diagnosis of FA and the severity of the clinical presentation (r= 0.66; p-value 0.009). Total serum IgE at baseline, along with the downward trend of food-specific IgE levels (to milk or egg), may be useful in the prognostication of natural tolerance acquisition.